-6-4y=3(y-10)

Simple and best practice solution for -6-4y=3(y-10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6-4y=3(y-10) equation:



-6-4y=3(y-10)
We move all terms to the left:
-6-4y-(3(y-10))=0
We calculate terms in parentheses: -(3(y-10)), so:
3(y-10)
We multiply parentheses
3y-30
Back to the equation:
-(3y-30)
We get rid of parentheses
-4y-3y+30-6=0
We add all the numbers together, and all the variables
-7y+24=0
We move all terms containing y to the left, all other terms to the right
-7y=-24
y=-24/-7
y=3+3/7

See similar equations:

| 1/2m+5/12=5/6 | | 6k+18=9 | | 2(2y+7)=24 | | 2(2y+7=24 | | 2√2x-1=3√2x+3 | | 32n^2-18=0 | | x-2x+4=-5-3x-8-4 | | 277=178+x | | 97-x=230 | | 105x-23=85x | | 2t=18/t | | .6x=195 | | 9x^2-27x+600=5x^2-24x+24 | | 2x^2+1x-351=0 | | X^x=2^2048 | | 3u-8=43 | | X+30+2x+10=180 | | 4x-6+2x=14 | | 3w+w=10 | | 36=15u-6u | | 10-3b+3=-11(b+2) | | x(.25)=150 | | X-4=3x-30 | | 3x-15=7x-6 | | 4^(x-3)=5x | | 7x-63=8x-6 | | 4^x-3=5x | | 4(3=t)=52 | | x-7=x+7 | | 4x+5-3=x+55(9-x) | | 3-11x=-188 | | x-(x*0.12)=500 |

Equations solver categories